KAJIAN KEPEDULIAN PEMERINTAH TERHADAP USAHA MIKRO, KECIL DAN MENENGAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT INDONESIA (Di Tinjau Dari Filsafat Ilmu) - Surya Budiman (Universitas Pamulang, 2014)
The study of Government Care to Micro, Small and Medium Enterprises in Developing Public Welfare of Indonesia Review by Philosophy of Science. Data’s consisted both primary data and secondary data. Primary data were obtained from the own thought sand observations by the author of the Micro, Small and Medium Enterprises. The secondary data obtained from the literatures, lectures and materials access from the Internet when making this assessment. The phenomenon showed that the lack of government attention to the micro, small and medium. Knowledge management of micro, small and medium enterprises is still lacking. Micro, small and Medium enterprise. It has a small capital, revenue and the narrow coverage area of operation. The results also indicate there is no government policy to improve the intensive knowledge to small people, either through seminars, training or any other way to improve the knowledge of micro, small and medium enterprise.In the philosophy of science, the government must to get the right ontology to improve people's welfare. The problem is in epistemology and axiology like how to improve the well-being of our society and we do not want to improve the welfare of the community. The author recommends to the government as an agent of development. The Government must have doing 5 things: the government must act as a Facilitator, Motivator, Stabilizers, motivator and regulator of the micro, small and medium enterprise. The government should make the right the political will and political power, where epistemology must be done correctly and in terms of axiology must provide benefits for small businesses, micro and medium enterprises to improve the welfare of all the people of Indonesia.Key world :UMKM, UUD 1945 ,Government Policy, Ontology, Epistemology, Aksiology.